Cysteine residues in signal transduction and its relevance in pancreatic beta cells - Holendova, Blanka; Plecita-Hlavata, Lydie (Frontiers in Endocrinology, 2023)
Cysteine is one of the least abundant but most conserved amino acid residues in proteins, playing a role in their structure, metal binding, catalysis, and redox chemistry. Thiols present in cysteines can be modified by post-translational modifications like sulfenylation, acylation, or glutathionylation, regulating protein activity and function and serving as signals. Their modification depends on their position in the structure, surrounding amino acids, solvent accessibility, pH, etc. The most studied modifications are the redox modifications by reactive oxygen, nitrogen, and sulfur species, leading to reversible changes that serve as cell signals or irreversible changes indicating oxidative stress and cell damage. Selected antioxidants undergoing reversible oxidative modifications like peroxiredoxin-thioredoxin system are involved in a redox-relay signaling that can propagate to target proteins. Cysteine thiols can also be modified by acyl moieties' addition (derived from lipid metabolism), resulting in protein functional modification or changes in protein anchoring in the membrane. In this review, we update the current knowledge on cysteine modifications and their consequences in pancreatic β-cells. Because β-cells exhibit well-balanced redox homeostasis, the redox modifications of cysteines here serve primarily for signaling purposes. Similarly, lipid metabolism provides regulatory intermediates that have been shown to be necessary in addition to redox modifications for proper β-cell function and, in particular, for efficient insulin secretion. On the contrary, the excess of reactive oxygen, nitrogen, and sulfur species and the imbalance of lipids under pathological conditions cause irreversible changes and contribute to oxidative stress leading to cell failure and the development of type 2 diabetes.